A Minireview on the Use of g-C3N4–Chitosan Biocomposite for Potential Applications - Santiago-Ramírez, C. R; Nair, Pooja R; Vela-Monroy, C. A; Aba-Guevara, C. G; Ramos-Delgado, N. A; Gracia-Pinilla, M. A (Frontiers in Materials, 2022)
The novel biocomposite based on graphitic carbon nitride (g-C3N4 (CN)) and Chitosan (CS) has been deeply studied and summarized in key points concerning various applications. The CN material is composed of the earth-abundant nature of C, N, and H, possesses excellent properties due to its two-dimensional structure, good chemical stability, and a narrow bandgap that allows its use in many applications. There is a lot of information on the role of CN as a potential photocatalyst, but not in association with other composites. In contrast, this minireview summarizes its applications not only in the field of photocatalysis but in all fields reported on the biocomposite of CN with CS. The incorporation of chitosan helps to overcome the existing limitations of CN, like low-surface area, low light absorption, fast recombination of charges, and hydrophobic character. To introduce, CS is an attractive biomaterial being a low-cost alternative for the preparation of films and catalysts due to its unique characteristics such as biodegradability, antimicrobial activity, and film-forming properties that increase the popularity of CN. In this current minireview, a comprehensive study was conducted on the properties, synthesis, and applications along with the advancements of CN incorporated with CS. Finally, we hope to stimulate researchers to study the biocomposite of CN and CS to find new portals and ways to develop effective materials.